On generalizations of regular-Lindelöf spaces - Anwar Jabor Fawakhreh; Adem Kiliçman (International Journal of Mathematics and Mathematical Sciences, 2001)
We study nearly regular-Lindelöf, almost regular-Lindelöf and weakly regular-Lindelöf spaces. Characterizations and some properties for these spaces are proposed. Relations among them are also studied.